Cover Picture: Journal of Basic Microbiology. 8/2015. (23rd July 2015) - Unknown
<x xml:space="preserve">Abstract</x> Cover illustration: The nematophagous fungus Monacrosporium salinum penetrated Trichostrongylus colubriformis L3 at 32 h post‐capture. (Photo: Wei Liu, College of Life Science and Engineering, Northwest University for Nationalities, Lanzhou, China)